Letter to the editor regarding “Diatoms in lung tissue: first investigation in Brazil in proving death by drowning” - Tironi, Fabio Antonio (Revista Brasileira de Criminalística, 2018)
1. LETTER TO THE EDITOR Thank you for publishing the paper entitled “Diatoms in lung tissue: first investigation in Brazil in proving death by drowning”, by Carneiro, et al., 2017 [1].